2002
DOI: 10.1002/ijc.10435
|View full text |Cite
|
Sign up to set email alerts
|

Expression and functional analysis of the anaplastic lymphoma kinase (ALK) gene in tumor cell lines

Abstract: The initial identification of the ALK gene, expressed as C-terminal part of the transforming fusion protein NPM-ALK in the t(2;5)(p23;q35) lymphoma-associated chromosomal translocation, revealed a novel receptor tyrosine kinase (RTK). In order to expand the knowledge on ALK expression in the human system, we examined a panel of human cell lines for ALK expression and found that transcription is completely repressed in cell lines of entodermal origin (0/21). Furthermore, full length receptor expression is absen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
100
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(104 citation statements)
references
References 38 publications
2
100
0
2
Order By: Relevance
“…Although ALK expression was previously demonstrated in a few ES cell lines and patient samples, these studies lacked the power to accurately determine the frequency of ALK upregulation and its association with patient outcome. 18,19 We demonstrated that MET is ubiquitously expressed in ES. The majority of tumors showed medium to high levels of cytoplasmic MET and apparent membranous staining was detected in several samples as well.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Although ALK expression was previously demonstrated in a few ES cell lines and patient samples, these studies lacked the power to accurately determine the frequency of ALK upregulation and its association with patient outcome. 18,19 We demonstrated that MET is ubiquitously expressed in ES. The majority of tumors showed medium to high levels of cytoplasmic MET and apparent membranous staining was detected in several samples as well.…”
Section: Discussionmentioning
confidence: 89%
“…16,17 In addition, ALK mRNA and/or protein expression was demonstrated in ES cell lines (4/4) and ES tumor samples (6/10), although the sample size was rather small. 18,19 No correlation between ALK expression and clinical outcome has been described in ES at present.…”
mentioning
confidence: 97%
“…However, ALK was originally discovered when it was found that the chimeric N-terminal nucleophosmin (NPM) domain/cytoplasmic (catalytic) ALK domain fusion protein (NPM-ALK) is the oncoprotein underlying the pathogenesis of anaplastic large cell lymphomas (ALCL) [5,6]. NPM-ALK results from the (2;5) (p23;q35) chromosomal translocation, however, other translocations also lead to constitutive activation of ALK and other malignancies and furthermore, wild-type ALK has been postulated to be involved in the pathogenesis of rhabdomyosarcomas [7], neuroblastoma and neuroectodermal tumors [8,9], glioblastomas [10], and melanomas [11].…”
Section: Introductionmentioning
confidence: 99%
“…Based on our recent findings that inappropriate expression of Ptn in transgenic mice stimulates breast cancer progression (Chang et al Submitted 2 ), that PTN signaling may be important in breast cancer [22], and that PTN activates the potent oncoprotein ALK through the PTN/ RPTPβ/ζ signaling pathway in PTN-stimulated cells (Perez-Pinera et al 1 ), we explored different databases to learn whether ALK is expressed in human breast cancers; only a single manuscript described ALK expression in breast cancer cell lines using RT-PCR [11]. The significance of the transcripts of ALK detected by PCR is unknown and, in the database search, we failed to uncover that ALK is expressed in human breast cancer tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Full-length ALK was initially described as an orphan receptor tyrosine kinase that shows restricted tissue distribution and is regulated during organ development (Iwahara et al, 1997;Morris et al, 1997). Several studies show expression of full-length ALK protein in cultured fibroblasts and endothelial cells as well as cell lines derived from epithelial cancers such as pancreatic and breast carcinoma (Stoica et al, 2001 and the neuroectoderm, that is, melanoma (Dirks et al, 2002), neuroblastoma Stoica et al, 2002) glioblastoma and non-Hodgkin's lymphoma (Delsol et al, 1997), reviewed by Pulford et al (2004).…”
Section: Introductionmentioning
confidence: 99%